The function of the Islamic tax system compared to the mainstream economics - Alireza Lashkari (جستارهای اقتصادی, 2021)
The tax system as a subset of the economic system serves the purposes that the economic system pursues. On the one hand, the goals of each system are based on the assumptions and values of each school, and therefore the fundamental function of tax systems cannot be more discrete than the underlying issues. The tax system of the Islamic Republic of Iran has witnessed changes in tax structures in recent years. A better understanding of the nature of the Islamic tax system and its functions may help to formulate and shape a more Islamic tax system. This paper examines the functions of a favorable Islamic tax system in comparison with the functions of the conventional economic tax system, using the content analysis approach, and therefore proposes some considerations for value added tax. This article uses the content analysis method of the functions of the favorable Islamic tax system in comparison with the functions of the tax system of the conventional economy and then, based on it, points about substituting the tawazon criterion in Islamic economic justice, tax principles, tax rates and bases, and share of taxes in government revenue sources. According to the Islamic policymaker, who considers justice as the basis of organizing society, taxes are also a tool for this purpose, and taxes that are compatible with achieving economic balance are considered appropriate. The balance criterion is considered in all the initial, process and final stages and the increase of tax revenues is followed by using justice-oriented methods and tax revenues can never be increased at the expense of justice. Also because in the economic system. Islam has part of the resources of wealth production (Anfal) at the disposal of the government.